COMPARATIVE ANTIBIOTIC RESISTANCE PROFILE OF THE MULTIDRUG RESISTANT E.COLI ISOLATED FROM COMMERCIAL AND BACKYARD POULTRY - F. Akhtar1; M. Rabbani; K. Muhammad; M. Younus; A. Ghafoor; A. A. Sheikh; A. Ahmad; J. Muhammad; A. Rasool; A. Y. Shaheen (Journal of Animal and Plant Sciences, 2016)
Community acquired multidrug resistant E. coli has become an emerging issue worldwide. The present study was planned to compare the antibiotic resistance profile of E. coli isolated from commercial broilers and backyard poultry reared in close proximity to human population. Out of 200 cloacal swabs (100 each from commercial broiler & backyard poultry), 126 samples (n=70 commercial broiler, n=56 backyard poultry) were found positive for E. coli through 16S rRNA PCR. The percentage of multidrug resistant E. coli isolates from commercial broiler chicken and backyard poultry were 64.2% and 53.5% respectively. Overall high antibiotic resistance was observed against Amoxycillin and Tetracycline with percentage resistance of 71.4% and 57.1% in commercial broiler, whereas 80.3% and 82.1% in backyard poultry respectively. The percentage resistance against Streptomycin and Sulphamethoxazole/Trimethoprim was observed to be high in backyard poultry (64.2% and 53.5%) as compared to the commercial broiler (28.5% and 35.7%) respectively. Percentage resistance against cephalosporin like ceftriaxone, cefaclor and ceftiofur was low both in case of backyard poultry and commercial broilers. Statistical analysis reveals that significant association exists between poultry species and antibiotic resistance of Oxytetracyclin, Streptomycin, Sulphamethoxazole/Trimethoprim, ceftriaxone, cefaclor and ceftiofur(p<0.05). The present study revealed that the trend in antibiotic resistance percentage is increasing in the backyard poultry as compared to the commercial poultry, which is possibly due to their close community interaction.
Keywords: Backyard poultry; E. coli; Multidrug resistant; 16S rRNA PCR